Intepretasi Tindak Tutur Penggunaan Ragam Bahasa Model Martin Joos pada Berita Online - Nuryansyah Adijaya; M. Yanuardi Zain; Febriyantina Istiara; Dayana, Yuliana Fatima (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
Interpretation in communication plays an important role in understanding the message conveyed in every utterance. However, disagreements sometimes arise because the receiver of the message interprets the utterance differently. This study aims to delve deeper into the interpretation of speech acts in the use of language varieties, particularly the use of frozen language variety in online media reporting. A qualitative descriptive method is used in this research to discuss the interpretation of the use of frozen language variety. The results of this study indicate that the use of frozen language varieties such as the words "sultan," "baginda," and "paduka" can be interpreted not only to indicate a degree of honor but also as satire to mock someone. One piece of evidence is when a governor was addressed as "baginda," and he responded to the greeting with displeasure. Another example is when a ministry was dubbed the "sultan ministry," which indicates a satire or criticism of the institution. This shows that language varieties, especially frozen language, can have different interpretations depending on the social, cultural, and value context in society.